THE RECOMBINANT ANTIGENS FOR VACCINES FOR THE TREATMENT OF PAPILLOMAVIRUS (REVIEW) - M. A. Zhuchenko (Разработка и регистрация лекарственных средств)
Two licensed vaccines Gardasil and Cervarix, containing main capsid protein L1 virus-like particles antigen, are used for prevention of diseases associated with human papilloma virus. L1 cannot provide protection against all pathogenic strains of HPV, shows low efficacy in middle and old age vaccinated patients, and are not therapeutically effective. The next generation of vaccines that contain minor protein L2 conserved epitopes as well as oncoproteins E6 and E7 promise to provide broad protection against all HPV, and prevent the emergence and spread of skin lesions.